We first : how brands and consumers use social media to build a better world - Mainwaring, Simon (Tantor Media, 2011)
Social media expert Simon Mainwaring details a visionary new practice in which brands leverage social media to earn consumer goodwill, loyalty, and profit while creating sustainable social change.